IDENTIFIKASI DRUG RELATED PROBLEMS (DRPs) DALAM PENGOBATAN DEMAM BERDARAH DENGUE PADA PASIEN ANAK DI INSTALASI RAWAT INAP RSUD KOTA MADIUN PERIODE JANUARIâ€“FEBRUARI 2015 - Nur Wijayanti, Andita (Widya Warta, 2017)
Drug Related Problems (DRPs) is an unexpected incident patients experience consequences or unforeseen consequences could potentially interfere with drug therapy to therapy outcomes. Dengue Haemorhagic Fever (DHF) is one of diseaseÂ  that occur in children and have a great chance to be the occurrence of DRPs. This study was aimed at determining the percentage of DRPs. This study was designed using non-experimental descriptive method with retrospective data collection obtained from medical records of DHF patients at RSUD Madiun from January to February 2015. The number of pediatric patients diagnosed with DHF was 58 patients and the number of samples fulfilling the inclusion criteria was 31 patients. The result showed that there were 4 categories out of 8 DRPs categories; they were untreated indication (31,25%), drug use without indication (15,63%), improper drug selection, (6,25%) and under dosage (21,88%).